Reconstructing the Demographic History of the Human Lineage Using Whole-Genome Sequences from Human and Three Great Apes - Hara, Yuichiro (Oxford University Press, 2012)
The demographic history of human would provide helpful information for identifying the evolutionary events that shaped the humanity but remains controversial even in the genomic era. To settle the controversies, we inferred the speciation times (T) and ancestral population sizes (N) in the lineage leading to human and great apes based on whole-genome alignment. A coalescence simulation determined the sizes of alignment blocks and intervals between them required to obtain recombination-free blocks with a high frequency. This simulation revealed that the size of the block strongly affects the parameter inference, indicating that recombination is an important factor for achieving optimum parameter inference. From the whole genome alignments (1.9 giga-bases) of human (H), chimpanzee (C), gorilla (G), and orangutan, 100-bp alignment blocks separated by ≥5-kb intervals were sampled and subjected to estimate τ = μT and θ = 4μgN using the Markov chain Monte Carlo method, where μ is the mutation rate and g is the generation time. Although the estimated τ(HC) differed across chromosomes, τ(HC) and τ(HCG) were strongly correlated across chromosomes, indicating that variation in τ is subject to variation in μ, rather than T, and thus, all chromosomes share a single speciation time. Subsequently, we estimated Ts of the human lineage from chimpanzee, gorilla, and orangutan to be 6.0–7.6, 7.6–9.7, and 15–19 Ma, respectively, assuming variable μ across lineages and chromosomes. These speciation times were consistent with the fossil records. We conclude that the speciation times in our recombination-free analysis would be conclusive and the speciation between human and chimpanzee was a single event.